2020
DOI: 10.1080/2090598x.2020.1716293
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of clinical and functional outcomes of artificial urinary sphincter implantation in women with stress urinary incontinence

Abstract: Objective: To evaluate the complications and results of artificial urinary sphincter (AUS) implantation in women with stress urinary incontinence (SUI). Methods: A selective database search using keywords (1990-2019) was conducted to validate the effectiveness of the AUS in women. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were utilised. The meta-analysis included 964 women (15 studies) with persistent SUI. The Newcastle-Ottawa score was used to determine the quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
(66 reference statements)
1
2
0
Order By: Relevance
“…The study reported complete continence rates of 61% to 100% at mean follow-up of 5 to 204 months, and the authors concluded that AMS-800 AUS can provide excellent functional outcomes in female patients with SUI resulting from ISD but at the cost of a relatively high morbidity. Explantation and mechanical failure rates in this analysis were similar to that reported by Barakat et al, 31 and urethral erosion rate varied from 0% to 22%. This series specifically noted intraoperative bladder neck and vaginal injury rates of 0% to 44% and 0% to 25%, respectively.…”
Section: Special Casessupporting
confidence: 88%
See 1 more Smart Citation
“…The study reported complete continence rates of 61% to 100% at mean follow-up of 5 to 204 months, and the authors concluded that AMS-800 AUS can provide excellent functional outcomes in female patients with SUI resulting from ISD but at the cost of a relatively high morbidity. Explantation and mechanical failure rates in this analysis were similar to that reported by Barakat et al, 31 and urethral erosion rate varied from 0% to 22%. This series specifically noted intraoperative bladder neck and vaginal injury rates of 0% to 44% and 0% to 25%, respectively.…”
Section: Special Casessupporting
confidence: 88%
“…Three recent meta-analyses specifically evaluating non-neurogenic SUI provided insight into the role of the AUS in the treatment of non-index SUI patients. Barakat et al 31 performed a systematic review of 15 studies (n=964) in women with persistent SUI following unspecified anti-incontinence treatments. Success rates and complications supported AUS as an effective treatment in women with severe UI after failure of first-line therapy.…”
Section: Special Casesmentioning
confidence: 99%
“…[12] It is difficult to make a direct comparison between the studies because of the heterogeneous groups and the fact that most of the studies were retrospective. As a result of this, there is still no evidence supporting the efficiency of the AUS in women who have SUI [13].…”
Section: Patient Selection and Outcomesmentioning
confidence: 95%